Long-term complications after tonsil surgery: an analysis of 54,462 patients from the Swedish Quality Register for Tonsil Surgery - Odhagen, Erik; Alm, Fredrik; Axelsson, Sara; Hemlin, Claes; Nerfeldt, Pia; Stalfors, Joacim; Sunnergren, Ola (Frontiers in Surgery, 2023)
Objective: To evaluate long-term complications after tonsil surgery, using an exploratory retrospective cohort study design based on data from the Swedish Quality Register for Tonsil Surgery (SQTS). Methods: All patients registered in the SQTS between 1 January 2009 and 31 May 2021 were eligible for the study. In this study, the definition of long-term complication was a complication that lasted at least six months after surgery. The definition of a complication was an individual patient report, in free text format, of a remaining problem six months after tonsil surgery. Complications were categorized as Disturbed taste or sense of smell, Dysphagia, Miscellaneous and general symptoms and signs, Miscellaneous throat problems, Pain or discomfort in the mouth or throat, Problems with jaws or teeth, Problems with the ears or hearing, Problems with the nose or sinuses, Problems with throat secretions or throat clearing, Problems with voice or speech, or Sensory symptoms. A multivariable logistic regression analysis was used to identify independent predictors of long-term complications. Results: In total, 54 462 patients were included in the study. A total of 3780 patients (6.9%) reported one or more long-term complications. The most frequent long-term complications, with a plausible connection to the surgery, were found in the categories: Pain or discomfort in the mouth and/or throat (1.9%), Problems with throat secretions or throat clearing (0.8%), Dysphagia (0.6%), and Problems with voice or speech (0.6%). Tonsillotomy was associated with lower risk of long-term complications compared to tonsillectomy. Conclusion: This study suggests that subjective long-term complications after tonsil surgery in general are relatively common (6.9%). However, the prevalence of complications with a plausible connection to the surgery were less common (4.0%) and specific complications seem to be rather rare with no single specific problem reaching a prevalence of ≥0.6%.